Палеопатологія та діагностика цинги (на антропологічних матеріалах із давньоруського Києва) - Козак, О.Д.; Шульц, М. (Археологія, 2007)
Наведено найвичерпніший на цей час огляд критеріїв діагностики цинги за антропологічними матеріалами та інтерпретації поширення цього захворювання серед давнього населення України. В статье сведена система диагностики цинги, основанная на палеоантропологических материалах. Заболевание рассматривается как маркер диет и общего состояния здоровья древнего населения. Диагностика с помощью морфологических и гистологических методик апробирована на примере костных серий из городских кладбищ Киева X—XIII вв. Приведены возможные интерпретации распространенности следов цинги среди детей. Установлены наиболее вероятные причины этой болезни в средневековом городе: зимне-весенние голодания и авитаминозы, а также последствия длительных эпидемий инфекционных болезней. The article summarizes the system of diagnostics of scurvy based on paleoanthropological materials. The disease is viewed as a marker of diets and general state of health of ancient population. Diagnostics with the help of morphological and histological methods was approbated on anthropological assemblages from Kyiv city cemeteries of 10th—13th cc. The author presents the possibilities for interpretation of spread of scurry vestiges among the children. She also determines the most probable reasons of this disease in the mediaeval city, namely, season starvations and vitamin deficiency, as well as consequences of epidemics of infectious diseases.